An author co‐citation analysis: Examining the intellectual structure of e‐learning from 1981 to 2014. Issue 1 (2015) - McCoy, Chase; Yu, Amy; Ramazanova, Sabina
ABSTRACT: Despite the emergence of e‐learning trends, the author co‐citation analysis (ACA) method has not yet been used to analyze e‐learning extensively. This study applies ACA to analyze the collected literature on e‐learning from 1981–2015, with the goal of identifying the top intellectual areas in three time periods – 1981–1991, 1992–2002, and 2003–2014 ‐ to provide a reference framework for future researchers. Therefore, the objective of this paper is to construct an intellectual framework in the field of e‐learning.